Early loading of implants with fixed dental prostheses in edentulous mandibles: 7.2-year clinical results from a prospective study - Kappel, Stefanie; Bernhart, Gunda; Eiffler, Constantin; Hassel, Alexander J.; Lehmann, Franziska; Rammelsberg, Peter (Clinical implant dentistry and related research, 2014)
Purpose: The purpose of this prospective follow-up study was to evaluate survival and success of early-loaded implants placed in the edentulous mandible and the survival of the fixed dental prostheses (FDPs) after in mean 7.2 years. Materials and Methods: Thirty-seven patients (mean age 64.5 years, 18.9% male) received 185 implants in the intraforaminal area of the edentulous mandible (five implants per patient). Within 2 weeks, all implants were early loaded with fixed dental prostheses. The patients were recalled once a year for clinical and radiographic examinations. The 17 patients (79 implants) attending the recall in 2012 were additionally asked for their satisfaction of functional and aesthetic aspects. Results: During a mean observation time of 7.2 years, 20 implants were lost in 11 patients, resulting in implant survival of 89.2%. Eight of all implants (4.3%) had too much marginal bone loss to satisfy the criteria of success. A total of 19 prosthetic complications and aftercare measurements had to be performed between in mean 4.5 to 7.2 years of observation. The survival of the original FDPs decreased to 83.8%. Of the 17 patients attending the recall in 2012, a total 59.5% had a satisfactory oral hygiene. According to the criteria of Albrektsson, the success rate for the remaining 79 implants was 89.9% after in mean 11.7 years. Patient satisfaction for assessment of functional and aesthetic aspects was in median 9 and 8 on the numeric rating scales. Conclusion: Long-term observation of in mean 7.2 years showed satisfactory results for both implant and superstructure survival. Prosthetic complications were easy to repair in most cases, but patients' ability for oral hygiene was reduced after the longer observation period. Especially in elderly patients, their attitudes and manual skills should be considered when planning the design of a new superstructure.